Report of the high-level regional conference on land and conflict in the East and Horn of Africa - Intergovernmental Authority on Development (IGAD, 2022)
This is a summary of the deliberations, emerging issues and action points from the high-level regional conference on land and conflict in the East and Horn of Africa. The objective of the Conference was to facilitate the development of a regional agenda and national policy priorities in land conflict and governance in the region. The Conference facilitated discussion and understanding of the Sustainable Development Goal (SDG) Number 16 on peaceful and inclusive societies, access to justice and the building of effective institutions. The Conference included a session of the Chief Justices of the EAC region who shared good practices and lessons learned in the management and resolution of disputes and conflict around land-based natural resources. The Conference was organised and put together by the Government of Uganda which was the host, the Intergovernmental Authority on Development (IGAD), and the International Development Law Organisation (IGAD). Other institutions that were involved in the planning of the high-level conference included: Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises (SPARC) and the International Land Coalition (ILC).